Strengthening Commercial Court Judges’ Knowledge in Handling Patent Claim Disputes: A Comparison Between Japan and Indonesia. - Sulistyono, Joko; Hartiwiningsih, Hartiwiningsih; Handayani, I Gusti Ayu Ketut Rachmi; Katagiri, Kazuaki (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2025)
This study aims to identify the substantive challenges that Commercial Court judges face when making decisions in patent claim disputes within the Indonesian Commercial Courts. These difficulties arise from the close link between patent claims and novel technological inventions. In Indonesia, However, the performance of Alternative Dispute Resolution mechanisms for patent disputes has been underwhelming, and they do not appear poised to become the primary resolution approach. The research primarily relies on a literature review, but also includes interviews with Commercial Court judges in Central Jakarta, and Japanese Judges in Japan IP Court, and patent Examiner in Japan Patent Office, to confirm the findings. From this study, Japan's system, which involves Court Researchers and an Expert Committee, has been found to provide judges with greater confidence and expertise in handling patent disputes. The Japanese model incorporates technical experts who assist the court in understanding the complexities of patent claims and novel technological inventions, which helps the judges make more informed decisions. This paper will explore the key features of the Japanese patent litigation system and examine how they could be adapted to address the challenges faced by the Indonesian Commercial Courts.